Early juvenile stages of three jewfishes from the southeast coast of India - Bensam, P (Indian Journal of Fisheries, 2011)
Three stages each of Johneiops vogleri, Johnius carouna and / . carulta, all collected form bottom trawl catches off Tuticorin and Pono Novo have been described. An account of the changes undergone in the morphology and pigmentation is given. Certain notable differences between 2 younger stages of J. carulta described earlier are pointed out.